HUBUNGAN KETAHANAN PANGAN DAN STABILITAS KEAMANAN NEGARA (KRISIS PANGAN DI VENEZUELA) - Reni Arlyan (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
Problem of Food emerged as a Non-Traditional Secuirty (NTS) issue in the aftermath of the Cold War and was identified as one of the seven pillars of human security by the 1994 UNDP Report ‘New Dimensions’ in Security. Food security as ‘the means for all people at all times to have both physical and economic access to basic food’ and that food security is an entitlement. When the shortages food supply in a country, it will be an increasing the conflict civil society, so the stability of the state security being disrupted. The availability of adequate food supplies could become the core of social contact in all the country's political system.The food crisis in Venezuela resulted in civil conflict be increased. Venezuela is the world's oil producing countries but due to falling world oil prices, then became distracted State reception system. The political system came along with the economic crisis makes Venezuela in the worst condition.This economic crisis makes Venezuela experienced a food crisis, so many societies suffered famine and looting food even do violence to gain access the food. Finally, the conflict civil society occur due to the food crisis and the stability of the State security becomes disrupted. In this paper using descriptive analysis method that describes the relationship of food security in Venezuela that can be disrupt the stability of State security. In this paper, using the perspective of Food Securitization.This is based on a change in the subject of security not only on military issues but the extension of the concept security including the threat of food security within a country. Food can be utilized as a political weapon by states and can be characterized as a form and symbol of political power.